Crimes of power & states of impunity: the US response to terror - Welch, Michael (Critical issues in crime and society, 2009)
A post-9/11 world -- A new configuration of power -- Unlawful enemy combatants -- Guantanamo Bay -- Torture -- Ordering Iraq -- Collateral damage -- Governing through terror -- States of impunity